The Impact Of Service Quality, Product Quality, And After-Sales Service On Customer Satisfaction And Loyalty: A B2B Study At Pt Mig Sulawesi - Mochamad Abidzaar Ridho; Albari (Cita konsultindo, 2025)
This study aims to analyze the effect of service quality, product quality, and after-sales service on customer satisfaction and loyalty in the context of Business to Business (B2B) relationships at PT MIG Sulawesi. The respondents of the study consisted of 250 employees of client companies who actively interacted with PT MIG Sulawesi in the last two years. Data were collected using a Likert-based questionnaire and analyzed using the Structural Equation Modeling (SEM) method with the Smart PLS approach. The results of the study indicate that service quality, product quality, and after-sales service significantly affect customer satisfaction, which in turn has a positive impact on customer loyalty. These findings support the research hypothesis that improvements in these three variables can strengthen long-term relationships between service providers and B2B clients, and contribute to the literature on customer satisfaction and loyalty in the strategic commodity sector.